The Task Force Report - Montague, J. (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1970)
The author gives a philosophical analysis of the general tenor of the Woods' Report, and provides a brief appraisal of its observations, particularly in regard to collective bargaining.